Corrosion resistance of a cast steel overpack for high‐level radioactive waste disposal in Japan. Issue 1 (23rd November 2020) - Ogawa, Yusuke; Suzuki, Satoru; Taniguchi, Naoki; Kawasaki, Manabu; Suzuki, Hiroyuki; Takahashi, Rieko
Abstract: The corrosion rate and stress corrosion cracking (SCC) susceptibility of a cast steel are studied for its application to metal containers (namely overpacks) for geological disposal of high‐level radioactive waste. Specimens for corrosion tests are cut from a prototype overpack manufactured by full‐scale casting. Casting defects are widely distributed in the prototype overpack; however, the flat‐bottom hole equivalent diameters for all defects detected by an ultrasonic test are 3.6 mm or less, which is relatively small. Forged steels and rolled steels are also tested for comparison of their corrosion properties with the cast steel. The corrosion rates are obtained by immersion tests in bentonite saturated with synthetic seawater under anaerobic conditions at 80°C for up to 1 year. The corrosion rate for the cast steel calculated by the weight loss during the experiments is close to that for the forged steels and rolled steels. The SCC susceptibility is examined using slow strain rate tests in a 1.5‐mol L −1 carbonate–bicarbonate solution, in which the occurrence of high‐pH SCC is often reported for carbon steels. The SCC susceptibility increased with the increase in the carbon content of the products; however, there are no clear differences between casting and forging. Abstract : The distribution of casting defects, the corrosion rate and the stress corrosion cracking (SCC) susceptibility of a cast steel were studied for the application of the cast steel, which has advantages over forged steels in terms of production time and cost, to a metal container for geological disposal of high‐level radioactive waste. The corrosion rate and the SCC susceptibility of the cast steel were not appreciably inferior to that of forged steels.